The Tragedy of the Aral Sea and its Impact on Human Life - Nuriddinov Komron Nodir og‘li; Ashurov Otabek Shavkatovich (American Journal of Bioscience and Clinical Integrity, 2025)
The drying of the Aral Sea has led to serious environmental changes and caused significant health problems among the local population. Ecological factors arising from the shrinking of the Aral Sea — such as declining water levels, accumulation of pesticides in the environment and food chains, dust storms, and changes in air quality — negatively affect human health.